The last kingdom [compact disc, unabridged] - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2023)
In a race across Bavaria for clues hidden in King Ludwig II's three castles, Cotton Malone and Luke Daniels battle a growing list of deadly adversaries, all intent on finding the last kingdom.